Catalytic conversion of methanol/ethanol to isobutanol – a highly selective route to an advanced biofuel. Issue 29 (21st March 2016) - Wingad, Richard L.; Bergström, Emilie J. E.; Everett, Matthew; Pellow, Katy J.; Wass, Duncan F.
Abstract : Catalysts based on ruthenium diphosphine complexes convert methanol/ethanol mixtures to the advanced biofuel isobutanol, with extremely high selectivity (>99%) at good (>75%) conversion via a Guerbet-type mechanism. Abstract : Catalysts based on ruthenium diphosphine complexes convert methanol/ethanol mixtures to the advanced biofuel isobutanol, with extremely high selectivity (>99%) at good (>75%) conversion via a Guerbet-type mechanism.